ANALYSIS OF BLOOD GLUCOSE LEVELS IN PEOPLE WITH TYPE II DIABETES MELLITUS (DM) AGED 50-60 YEARS WITH GLUCOMETER METHOD AT ISLAMIC MALAHAYATI MEDAN HOSPITAL YEAR 2022 - Siahaan, Maniur Arianto; Aruan, Dyna Grace (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Diabetes Mellitus (DM) type II is a metabolic disorder disease characterized by an increase in blood glucose due to a decrease in insulin secretion by pancreatic beta cells or impaired insulin function (insulin resistance). Blood glucose is a carbohydrate that circulates in the body in the metabolic process. Monitoring blood sugar levels is needed in establishing a diagnosis, especially for Diabetes Mellitus (DM). Blood glucose levels can be checked when the patient is in a fasting condition or it can also be when the patient comes to check, with the results of the examination of blood glucose levels when >200 mg / dl, while for the results of glucose levels during fasting >126 mg / dl.. This type of research is descriptive. A tool to measure blood glucose levels using the Glucometer Method. The time of the study was carried out from January to March at the Islamic Malahayati Medan Hospital’s Laboratory by taking 10 samples. Data collection is carried out by direct examination of blood glucose levels in patients with Diabetes Mellitus at Malahayati Medan Islamic Hospital in March-April 2022. From the results of examination of blood glucose levels in 10 samples of type II diabetes mellitus (DM) aged 50-60 years with glucometer method at Malahayati Islam hospital Medan 2022 obtained the results that all samples showed an average blood glucose level value above 220 mg / dl and increased from its normal value. Keywords: Diabetes Mellitus; Blood Glucose Level